III-Nitride nanowire optoelectronics. (November 2015) - Zhao, Songrui; Nguyen, Hieu P.T.; Kibria, Md. G.; Mi, Zetian
Abstract: Group-III nitride nanowire structures, including GaN, InN, AlN and their alloys, have been intensively studied in the past decade. Unique to this material system is that its energy bandgap can be tuned from the deep ultraviolet (~6.2 eV for AlN) to the near infrared (~0.65 eV for InN). In this article, we provide an overview on the recent progress made in III-nitride nanowire optoelectronic devices, including light emitting diodes, lasers, photodetectors, single photon sources, intraband devices, solar cells, and artificial photosynthesis. The present challenges and future prospects of III-nitride nanowire optoelectronic devices are also discussed.